Pariwisata Kreatif Pada Argowisata Perkebunan Teh Gunung Manik Desa Karyamukti Kabupaten Cianjur - Raflyanto Athallah; Rehulina Apriyanti (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2023)
The tea plantation located in the Karyamukti Village location is a tea plantation owned by Perhutani West Java and used as HGU land by PT Sinar Sosro. Agricultural agrotourism is a form of tourism that offers agricultural activities as the main attraction, takes advantage of artificial natural beauty, and involves the surrounding community as the manager of the tourist area. In addition, "creative tourism is tourism that offers visitors a variety of creative experiences. So that the tea plantation located in Karyamukti Village will design a creative tourism concept for the Gunung Manik Tea Plantation agrotourism, create attractions for tourists to provide an experience of interaction between tourists and the community, and make Karyamukti Tourism Village have a new form of vehicle for tea plantation tourism that carries a creative tourism concept.